Metabolic Dysfunctions in Amyotrophic Lateral Sclerosis Pathogenesis and Potential Metabolic Treatments - Tefera, Tesfaye W.; Borges, Karin (Frontiers in Neuroscience, 2017)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease primarily characterized by loss of motor neurons in brain and spinal cord. The death of motor neurons leads to denervation of muscle which in turn causes muscle weakness and paralysis, decreased respiratory function and eventually death. Growing evidence indicates disturbances in energy metabolism in patients with ALS and animal models of ALS, which are likely to contribute to disease progression. Particularly, defects in glucose metabolism and mitochondrial dysfunction limit the availability of ATP to CNS tissues and muscle. Several metabolic approaches improving mitochondrial function have been investigated in vitro and in vivo and showed varying effects in ALS. The effects of metabolic approaches in ALS models encompass delays in onset of motor symptoms, protection of motor neurons and extension of survival, which signifies an important role of metabolism in the pathogenesis of the disease. There is now an urgent need to test metabolic approaches in controlled clinical trials. In addition, more detailed studies to better characterize the abnormalities in energy metabolism in patients with ALS and ALS models are necessary to develop metabolically targeted effective therapies that can slow the progression of the disease and prolong life for patients with ALS.